Cash holdings, corporate governance and firm performance in hospitality industry / Kwan Jing Hui - Kwan , Jing Hui (2018)
This thesis consists of three essays on corporate cash holdings. The central theme of the dissertation is to study the impact of internal and external corporate governance mechanisms on firms’ corporate cash management policy, and firm performance in the hospitality industry. The first essay of the dissertation examines the determinants of cash holdings using a sample of public listed hospitality firms in Malaysia firms from year 2002 to 2013. The non-parametric Wilcoxon-Mann-Whitney test was carried out to examine the time and sectoral differences in cash holdings. In addition, the panel regression techniques are used to investigate the relationships between firm characteristics and level of corporate cash holdings. The result revealed that larger and higher leveraged companies have lesser cash. Similarly, capital expenditures and liquid assets substitutes are found to have a negative effect on the level of cash. However, the cash flow, cash flow variability, growth opportunities and, dividend dummy were found to have a positive relationship with cash holdings decision. The result shows that cash holdings theories such as trade-off theory, the pecking order theory, and the agency theory, help explain corporate cash holdings behaviour of firms in emerging market, such as Malaysia. Besides, the findings show a significant impact of the tourism crisis on cash holdings in the industry. The second essay studies the relationships between corporate governance mechanisms and cash holdings, and joint effects on firm performance at the firm level. Using a panel data analysis of a sample of public listed hospitality firms in Malaysia and Singapore during the period from 2002 to 2013, the relationship between corporate governance and cash holdings is investigated. The results show that characteristics such as board duality and large board size are significantly related to corporate cash policies. The paper provides important evidence that corporate cash serves as a valuable strategic asset, especially during a crisis. This study finds that the relationship between firm performance and cash holding are significantly moderated during tourism crisis. The results show that the stock market places a higher value on corporate cash holdings during the sudden crisis. Finally, the third essay presents a cross-country study using 1274 firm-year observations from 2001 to 2013 from public listed hospitality firms in ASEAN to test the impact of corporate governance on cash holdings. The relationship between external governance mechanism and cash holdings behaviour of firms at country-level are studied. The results show positive and significant relationship between the country-level control of corruption, regulatory quality, the rule of law, and corporate liquidity. However, there is no significant relationship between country-level political stability, voice and accountability and corporate liquidity. Further investigation was carried out to test the effect of tourism crisis and corporate liquidity. The results shall benefit various parties including the legislators and policy makers. Not only it serves as a strategic deterrence, but also helps firms to gauge opportunities.